Acerola (Malpighia emarginata) pulp: characterization and stability of anthocyanins under different conditions - OLIVEIRA FILHO, Josemar Gonçalves de; ESTEVAM, Elisangela Barbosa Borges; LEMES, Raiane Silva; PRADO, Danielle Maria Fernandes do; SILVA, Vanessa Paula da; SILVA, Lilian dos Santos; DUARTE, Larissa Graziele Rauber; EGEA, Mariana Buranelo (Food Science and Technology, 2023)
Tropical fruits provide a high economic potential and their inclusion in the diet can provide health benefits. In this sense, this study aimed to evaluate the proximal composition, bioactive compounds, antioxidant activity, and stability of anthocyanins of acerola pulp in the absence and presence of light at temperatures of 7 and 21.7°C. The results for the proximal composition (g/100 g) were 93.49 moisture, 0.04 protein, 0.09 lipid, 0.60 ash, and 6.28 carbohydrates, totaling a 28.29 kcal/100 g caloric value. For total bioactive compounds, the results were 3.22 µg/g chlorophyll, 29.71 µg/g carotenoids, 3.74 g/100 g flavonoids, and 6.12 mg/100 g phenolic compounds. Acerola pulp showed high antioxidant activity by DPPH and ABTS methods with values of 6.17 μmol/g and 3.19 mM TEAC/g, respectively. Regarding the stability of anthocyanins, in acerola pulp stored away from light and at a temperature of 7°C, these pigments remained more stable than when subjected to light and a temperature of 21°C. Thus, it was possible to perceive that, in addition to the acerola being important for the food industry, storage under low temperatures and the absence of light can contribute to greater stability of anthocyanin pigments.